(untitled) (ModaPalavra e-periódico, 2009)
The body is the object of study of this article. The reverse shows contemporary aesthetic ideal of the body in its transformation, construction and the reverse process. Its evolution over time, demonstrating that it is in constant change. This on the advertising and the way it operates, is about the medicine and the advances in this area to make the body more young and attractive. This article deals with a different body, the identities that accept the most curves and wrinkles. Is a body with volume and history tell. This the way in which this body has been accepted for publication by the society and in a near future, the fashion.